Predicting Sukuk Default Probability and Its Relationship with Systematic and Unsystematic Risks: Case Study of Sukuk in Indonesia - Ardiansyah, Misnen; Qizam, Ibnu; Haron, Razali; Qoyum, Abdul (e-Journal International Journal of Research in Commerce, Economics & Management, 2013)
The objective of this research is to analyse comprehensively the default risk of sukuk in Indonesia. It discusses the analysis of default probability of sukuk in Indonesia bond market, and, to find the relationship of default probability of sukuk with the systematic and unsystematic risks. To achieve the objective, Merton model is used to identify the default probability of Sukuk in Indonesia. In addition, to find the systematic risk and unsystematic risk which have impact on sukuk default this research will use Panel data analysis will be used as a main tool analysis. The finding shows that there are two companies issuing sukuk with very high default risk, namely, PT Berlian Laju Tanker with average default probability of 74.456% and PT Pembangkit Listrik Negara which has a default risk by 61.339%. Comparatively, other sukuk has quite low default probability which is around 20% on average. Systematic and unsystematic variables are able to explain sukuk default. Money supply and the exchange rate are two systematic variables that could explain sukuk default. In addition, the unsystematic variables show that the solvency ratio (debt to equity ratio) and the profitability ratio (Return on Assets) have significant implications on default probability of sukuk. This study provides an original insight into understanding sukuk default in Indonesia and its determinant. It also contributes to the literature on Islamic finance especially in term of sukuk default.